Communication Training for Young People with Autism Spectrum Disorders: Evidence-Based Study - Fomina, E.A.; Suvorova, I.Y. (Autizm i narušenie razvitiâ, 2024)
Objectives. Psycho-educational programs for children and young people with autism spectrum disorders (ASD) are aimed to train social and daily skills. The value of emotional exchange often remains outside the focus of teachers. However, the depression and self-harmful behavior experienced by young people with ASD are explained as a lack of social motivation and internal emptiness. The goal of present article is to evaluate the effectiveness of communication training as a safe space for emotional exchange. Methods. The training is based on the idea of communication as a complex process of interaction, the dynamics of which is influenced by the experience of different type of relationships: mother-child, child-family, child-school, etc. The training involves work through each level of interaction. The trainig effectiveness was evaluated using a formative experiment aimed at assessment of changes in communication of young people with ASD. The experimental sample included 25 people with ASD aged 20 to 25 years (M = 22.7; SD = 1.7), 5 persons in each group. The control sample also included 25 people aged 21 to 25 years (M = 23.3; SD = 1.43). All participants are male. For the primary and control sections, observation units were developed: frequency of violation of social norms, number of completed communicative acts and frequency of social stress. For statistical processing, the Mann-Whitney U test and the Wil coxon W test were used. Results. Using the Wilcoxon W test, the effectiveness of the impact of communicative training on the experimental group was proven: violation of social norms (W = 325; p ≤ 0.01; d = 2.04), completed communicative acts (W = 115; p ≤ 0.01; d = 0.89), social stress (W = 244; p ≤ 0.01; d = 1.04). Using the Mann-Whitney U test, the insignificance of the influence of group dynamics on the training effectiveness indicators in the control group was proven: violation of social norms (U = 615; p ≤ 0.01; d = 3.24), completed communicative acts (U = 184, 5; p ≤ 0.01; d = 0.86), social stress (U = 453.5; p ≤ 0.01; d = 0.93). Conclusions. Consistent processing of experiences at the level of relationships: mother - child, child - family, child - school, etc. became an effective method for developing communication skills in young people with ASD. In the future, it is necessary to check the duration of the effect after the end of the training, as well as the transfer the acquired skills to other areas of life. Актуальность и цель. Коррекционные программы для детей и молодых людей с расстройствами аутистического спектра (РАС) часто направлены на научение социально-бытовым навыкам, и ценность эмоционального обмена нередко остается вне фокуса внимания педагогов. Вместе с тем переживаемые молодыми людьми с РАС депрессивные состояния зачастую объясняются отсутствием социальной мотивации. Представлена работа по оценке эффективности коммуникативного тренинга как безопасного пространства для эмоционального обмена. Методы и методики. В основе тренинга лежит представление об общении как о сложном процессе взаимодействия, на динамику которого влияет опыт выстраивания отношений мать - дитя, ребенок - семья, ребенок - школа и т.п. Тренинг предусматривает проработку каждого из уровней взаимодействия. Его эффективность проверялась с помощью формирующего эксперимента, нацеленного на диагностику изменений в коммуникации у молодых людей с РАС. В экспериментальную выборку включили 25 человек c РАС в возрасте от 20-ти до 25-ти лет (M = 22,7; SD = 1,7) по 5 в каждой группе. В контрольной выборке были также 25 человек от 21-го до 25-ти лет (M = 23,3; SD = 1,43). Все участники мужского пола. Для первичного и контрольного срезов были разработаны единицы наблюдения: частота нарушения социальных норм, количество завершенных коммуникативных актов и частота проявлений социального стресса. Для статистической обработки применялись U-критерий Манна-Уитни и W-критерий Вилкоксона. Результаты. С помощью W-критерия Вилкоксона доказана эффективность воздействия коммуникативного тренинга на экспериментальную группу: нарушение социальных норм (W = 325; p ≤ 0,01; d = 2,04), завершенные коммуникативные акты (W = 115; p ≤ 0,01; d = 0,89), социальный стресс (W = 244; p ≤ 0,01; d = 1,04). С помощью U-критерия Манна-Уитни доказаны существенные различия в показателях эффективности тренинга в контрольной и экспериментальной группах: нарушение социальных норм (U = 615; p ≤ 0,01; d = 3,24), завершенные коммуникативные акты (U = 184,5; p ≤ 0,01; d = 0,86), социальный стресс (U = 453,5; p ≤ 0,01; d = 0,93). Выводы. Последовательная проработка переживаний на уровне мать - дитя, ребенок - семья, ребенок - школа и т.п. на коммуникативных тренингах показала себя как эффективный способ развития коммуникативных навыков у молодых людей с РАС. В перспективе необходимо проверить длительность эффекта после окончания тренинга, а также перенос полученных навыков на другие сферы жизни.